Ejercicios de estabilización postural en pacientes post operativos de hernia que acuden al departamento de fisioterapia de la asociación de personas con discapacidad física de Chimborazo, perdido Marzo-Junio 2016 - Paca Aulla, Jessica Maribel (2016)
This research deals with postoperative hernia treatment in patients who come to the Association of People with Physical Disabilities of Chimborazo, following the intervention uses Physiotherapy. In these patients were detected that hernias are caused by poor posture adopted at work or outside, weakness in the paravertebral muscles, traumatic or degenerative injuries, overexertion and repetitive motion that produces pain in the lumbar region. After surgery for hernia it is operated 20% said they are on equal terms 70% feel better and the remaining 10% respondents feel very well. It also presents continuous pain in the lumbar region 50% while the remaining 50% occasionally. Patients who underwent surgery 17% state that the operation was conducted in the cervical region meanwhile 83% responds that the operation is performed in the lumbar region is still the highest incidence in patients. Stabilization exercises train the patient to control posturally destabilizing forces. These exercises may begin demanding postural stabilization and strain gauge of a key area such as the lumbar-pelvic junction during movements of the trunk or limbs, and may progress to include control of the lumbar-pelvic posture during functional activities such as sitting, rise, bending, etc. The main objective of this program is the recognition of the key stabilizers by improving strength and resilience, while insisting on proper neuromuscular control and coordination. Training stabilization, is a progressive exercise program designed to reverse the effects of deconditioning or to maximize the potential yield.